2022
DOI: 10.3389/fgwh.2022.871090
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perceptions and Attitudes Toward HPV Vaccination: A Survey on Parents of Girls Aged 11–18 Years Old in Greece

Abstract: ObjectiveTo investigate knowledge, perceptions and practices of parents of girls aged 11–18 years old in Greece toward HPV vaccination, and determine which factors are associated with parents' decision to vaccinate their daughters.MethodsA close-end questionnaire was constructed and telephone interviews were conducted upon informed consent. The sample was random, national, stratified by geographic region and representative of the general population of parents of girls aged 11–18. The data collected include: ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In line with this, results of systematic review from 2017 showed that Scotland had the highest uptake, while Hong Kong had the lowest, at 2.4% to 9.1% [ 22 ]. Like the study from Greece, many studies aimed to investigate knowledge, perceptions and practices of parents toward HPV vaccination, and determine which factors are associated with parents’ decision to vaccinate their daughters [ 23 ]. This was the first cross-sectional study carried out in Serbia considering parents’ motivation and attitudes for the HPV vaccination, when the HPV vaccine became available, free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, results of systematic review from 2017 showed that Scotland had the highest uptake, while Hong Kong had the lowest, at 2.4% to 9.1% [ 22 ]. Like the study from Greece, many studies aimed to investigate knowledge, perceptions and practices of parents toward HPV vaccination, and determine which factors are associated with parents’ decision to vaccinate their daughters [ 23 ]. This was the first cross-sectional study carried out in Serbia considering parents’ motivation and attitudes for the HPV vaccination, when the HPV vaccine became available, free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve the current situation, the provision of correct and adequate information by physicians and government officials, who are the main information sources for parents is important. These channels positively affect impressions of the HPV vaccine and are effective for improving parents’ knowledge of the HPV vaccine and the vaccine uptake, as evidenced in other previous reports as well [54] , [55] , [56] , [57] .…”
Section: Discussionmentioning
confidence: 54%
“…When comparing with the M1D0 group, the older the mother was, the higher the possibility of mother-daughter vaccination. Naoum’s study showed older parents had higher possibilities of vaccinating their daughters [ 29 ]. This may because older mothers have higher knowledge [ 30 ] and willingness to vaccinate their daughters [ 31 ].…”
Section: Discussionmentioning
confidence: 99%